Pengaruh Self Efficacy dan Etos Kerja terhadap Kepuasan Kerja pada Guru SD di Kecamatan Ketanggungan Kabupaten Brebes - Alif Nurfitrah; Azizah Indriyani; Dwi Harini; Indah Dewi Mulyani; Gian Fitrialisma (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
This study aims to analyze the influence of self efficacy and work ethic on the job satisfaction of elementary school teachers in Ketanggungan District, Brebes Regency. Teacher job satisfaction is an important aspect in creating a productive and sustainable educational environment. The approach used in this study is a quantitative approach with an associative type of research. The research population was 418 elementary school teachers, and as many as 204 teachers were selected as samples through probability sampling techniques using the simple random sampling method. Data collection was carried out using standardized questionnaires, and data analysis was carried out using multiple linear regression with the help of SPSS software. The results of the study show that self-efficacy has a positive and significant effect on teacher job satisfaction. Teachers who have high confidence in their abilities tend to be more satisfied in carrying out their duties and responsibilities. In addition, work ethic has also been proven to have a positive and significant effect on job satisfaction. Teachers with a high work ethic show dedication, responsibility, and work ethic that have an impact on increasing job satisfaction. Simultaneously, these two variables make a significant contribution to the level of teacher job satisfaction. These findings indicate that strengthening self-efficacy and instilling a good work ethic is an important strategy in increasing the job satisfaction of educators. The practical implications of this research can be a reference for education policy makers in designing teacher professional development programs.